Selfie tourism promotion to support innovative tourism in the era of disruption - Sari, Putu Ratna Juwita; Wisudawati, Ni Nyoman Sri; Yulianti, Ni Made Dhian Rani (International research journal of management, IT and social sciences, 2019)
In the current era of disruption, innovation and creativity are needed in all lines of business, including the Tourism sector. Wanagiri Village is one of the tourist destination areas which is located in Buleleng Regency is currently conducting promotions to attract tourists visiting this place. Having a strategic location and involving the community, the type of tourist attraction developed is a selfie tour by having lakes and mountains as background. Using SWOT analysis, it is expected to be able to find out which type of promotion is most appropriate to attract tourists. This study used a qualitative descriptive method, informants with purposive sampling, and triangulation of data aimed at obtaining data validity.